2012
DOI: 10.1016/j.ijgo.2012.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Detection of human papillomavirus genotypes associated with mucopurulent cervicitis and cervical cancer in Changchun, China

Abstract: Infection with HPV was prevalent among Chinese women with MPC or CC. Furthermore, the high prevalence of oncogenic genotypes observed among HPV-positive patients with MPC suggests that this group is at increased risk of developing CC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 12 publications
2
19
1
Order By: Relevance
“…The overall prevalence of HPV infection in the CC group (84.4%) was similar to the rate of 85.9% reported in a meta-analysis of CC in Asia (Bao et al, 2008b). Like other regions worldwide, HPV16 was the predominant type (55.8%, 43/77) identified among CC patients in the present study; very similar to the previously reported rate in a meta-analysis of HPV in mainland China and Hong Kong (58.7%) (Bao et al, 2008a), but it was significantly lower than the rate found in Changchun, China (87.7%, 57/65) (Liu et al, 2013). As we know, except for HPV16 appears most frequently, the probability of other genotype can vary in different countries or areas.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The overall prevalence of HPV infection in the CC group (84.4%) was similar to the rate of 85.9% reported in a meta-analysis of CC in Asia (Bao et al, 2008b). Like other regions worldwide, HPV16 was the predominant type (55.8%, 43/77) identified among CC patients in the present study; very similar to the previously reported rate in a meta-analysis of HPV in mainland China and Hong Kong (58.7%) (Bao et al, 2008a), but it was significantly lower than the rate found in Changchun, China (87.7%, 57/65) (Liu et al, 2013). As we know, except for HPV16 appears most frequently, the probability of other genotype can vary in different countries or areas.…”
Section: Discussionsupporting
confidence: 87%
“…The difference may partially be due to our method is more sensitive than that of they used. The prevalence of oncogenic HPV infection in this group was up to 88.1% (37/42), simlar to that (77.5%) of Liu et al (2013). HPV16, 58, 59-as oncogenic genotypes-were predominant in MPC group, indicative of MPC patients should be made aware of the danger of developing CC.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations